2023
DOI: 10.37360/blacpma.23.22.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Vicenin-2 and vitexin participate in the in vitromodulation of the anti-inflammatory and antioxidant activities exerted by two Urtica circularis extracts

Abstract: Urtica circularisis an Argentinean species traditionally used to treat inflammation symptoms and oxidative stress-related diseases. Considering the uses in folk medicine, the purpose of this work was to evaluate and compare the anti-inflammatory and antioxidant activities of two different U. circularisextracts. The contribution of vicenin-2 and vitexin, two compounds identified in the phytochemical analysis, in the biological activity of the extracts was evaluated. The anti-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…There are a wide variety of effects caused by the different chemical compounds. For instance, the flavonoids such as vitexin, which has been determined in Passiflora (Costa et al, 2016), possess an antioxidant and anti-inflammatory effect in vitro (Marrassini et al, 2023). A study of patients in Vietnam showed that those undergoing breast cancer cobalt-60 radiotherapy, vitexin administration produced a significant radioprotective effect on peripheral blood cell numbers and lymphocyte transformation function (Van Hien et al, 2002)., which coincides with a systematic review that included nine clinical trials with treatment from one day to 30 days in people over 18 years of age, where the effects of passionflower were measured using several different tests and scales reported in most studies reduced levels of anxiety after the administration of Passiflora incarnata preparations, with a less evident effect in people with mild symptoms of anxiety (Janda et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…There are a wide variety of effects caused by the different chemical compounds. For instance, the flavonoids such as vitexin, which has been determined in Passiflora (Costa et al, 2016), possess an antioxidant and anti-inflammatory effect in vitro (Marrassini et al, 2023). A study of patients in Vietnam showed that those undergoing breast cancer cobalt-60 radiotherapy, vitexin administration produced a significant radioprotective effect on peripheral blood cell numbers and lymphocyte transformation function (Van Hien et al, 2002)., which coincides with a systematic review that included nine clinical trials with treatment from one day to 30 days in people over 18 years of age, where the effects of passionflower were measured using several different tests and scales reported in most studies reduced levels of anxiety after the administration of Passiflora incarnata preparations, with a less evident effect in people with mild symptoms of anxiety (Janda et al, 2020).…”
Section: Discussionmentioning
confidence: 99%